Alanine as natural biopesticide from Mirabilis jalapa and its interaction with glutamate as an inhibitor in insects immune system - Dina Maulina; Mohamad Amin; Sri Rahayu Lestari; Muhammad Aziz (The East Java Biological Society, 2018)
Alanine is a secondary metabolic secretion from Mirabilis jalapa. It is used as a modulation of natural pesticide compound. Alanine is predicted to act as an inhibitor compound in the defense mechanisms in the insect body. This study investigated the modeling structures and the protein receptor from alanine in the immune system mechanism and their optimization of the effectiveness as biopesticides to the insects. This research was conducted using an in silico modeling through the reverse docking stage, including the collection of 3D structures of natural compounds, prediction of target protein, receptor profiling, clarification of the potential of alanine compounds based on mode of action with PyRx 0.8 software, and interaction visualization between alanine compounds with the target protein using PyMOL and LigPlus+ software. The results showed that the alanine compounds from M. jalapa plants have targeted well the glutamate receptors in the insects. Both alanine and glutamate compounds have the same interactions with the glutamate proteins receptor shown by the Van der Waals interaction, e.g. the hydrogen bonding on certain amino acids has binding affinity of -15.889 kJ/mol. The interaction between alanine and glutamate affects the signal transduction cascade at the cellular level due to a neuromuscle and olfactory inhibitor. In addition, the continuous interruption of signal transduction affects the dysfunctional immune system of the insect body leading to their mortality.